A LITERATURA INFANTO-JUVENIL NA CONTEMPORANEIDADE: OUTRO OLHAR PARA O LITERÁRIO EM SALA DE AULA - Santos David, Ricardo (LINKSCIENCEPLACE, 2026)
Through an objective view of how the Brazilian literature today is whether it is possible to verify that current literary crisis can only be tackled if we know the taste of preteens and change our relationship with the students, with regard to the reading of the stimulus . This study aims, dealing with children's literature in the contemporary, demonstrating the challenges faced by teachers, the applicability of the "love of reading" in school practice and in the lives of children and adolescents of today. To conduct this study, I used me bibliographic and exploratory research, demonstrating how the school can contribute to the formation of readers who read for pleasure and satisfaction. Seeking to address the issue from the historical aspect to contemporary reflecting on possible solutions to difficult to introduce reading in the lives of children and youth.